(untitled) (Perioperaciina Medicina, 2018)
Liver rupture most commonly occurs because of a blunt abdominal trauma. We present a case of peliosis hepatis in a postpartum patient who developed hemoperitoneum due to spontaneous hepatic rupture from this rare liver condition. Physicians should be aware of this rare condition in patients with non-traumatic liver rupture and with hemoperitoneum. Peliosis hepatis is most often asymptomatic and incidentally found during autopsy. It comes to the surgeon’s attention just after the spontaneous rupture of the lesion, resulting in a massive hemoperitoneum. Peliosis hepatis should always be considered in the differential diagnosis of sudden intraperitoneal hemorrhage, especially when the cause of hepatic rupture is unknown.